THE INFLUENCE OF TRANSMISSION OF DUAL MONETARY SYSTEMAND FINANCIAL RATIO TO THE FINANCING TO DEPOSIT RATIO (FDR) OF ISLAMIC BANKS IN INDONESIA (2004 – 2011) - AM Hafidz MS (Jurnal Hukum Islam, 2012)
Abstract: This paper aims to determine the factors in transmission dual monetary system and financial ratios that influence the FDR of Islamic banks. The study will use a quantitative approach. The analysis method uses multiple linear regression to test whether the eight independent variables have an effect and associated with FDR. By using an alpha value of 0.10 It is known that there are three independent variables that have a significant effect towards FDR of Islamic banks, namely BI Rate, inflation and DPK. Five independent variables others, namely placement in SBI Syariah, nisbah, CAR, NPF and BOPO are not has a significant effect on the FDR of sharia banks. The F test shows that the independent variable simultaneously influences the dependent variable, because of the value probability F-statistic is smaller than 0.05. Of the eight independent variables used, there are five independent variables that are positively related to FDR Islamic banks, namely ratio, inflation, CAR, DPK and NPF. Meanwhile, three variables others, namely the BI Rate, placement on SBI Sharia and BOPO are related negative towards the FDR of Islamic banks during the scope of this research.